Effect of Nano-Silica on Mechanical Properties and Cytotoxicity of Calcium-Silicate-Based Root Canal Filling Materials - Hao He; Bolang Hao; Xiang Xiong; Yi Cheng; Jia Lou; Zheyu He; Dongyang Li; Zhihuan Wang; Jian Qin (Crystals)
A study was conducted to evaluate the effect of nano-silica (NS) content on the strength and cytotoxicity of calcium-silicate-based root canal filling materials. In this experimental laboratory study, four types of calcium-silicate-based paste with different NS ratios were prepared and hydrated for seven or 28 days. The setting times, compressive strengths, and porosities were tested to determine the properties of the pastes. The residual NS and the calcium hydroxide (CH; Ca (OH)2) content were investigated to analyze the hydration products. The experiments demonstrated that NS facilitates the hydration of calcium-silicate-based materials, enhances the formation of hydration products, and ensures effective porosity filling. Consequently, these findings suggest that NS contributes to the enhancement of the early compressive strength of calcium silicate root canal filling pastes. The addition of 9% NS enhanced the early compressive strength by 41.99% compared with the NS-free samples. Additionally, it was found that the test group without NS, as well as the test groups with 3% and 9% NS, exhibited mild cytotoxicity, while the test group with 15% NS exhibited moderate cytotoxicity. The observed cytotoxicity can be attributed to the increase in the ambient pH due to the production of CH during hydration. The findings of this study demonstrate that the early compressive strength of calcium-silicate-based root canal filling materials exhibits a substantial increase in response to the incorporation of NS, and that calcium-silicate-based root canal filling materials do not manifest significant levels of toxicity. NS improved hydration product formation and made efficient pore filling possible.